Front Cover: Enhanced Electrochemiluminescence of A Macrocyclic Tetradentate Chelate Pt(II) Molecule through Its Collisional Interactions with the Electrode (Chem. Asian J. 20/2022). Issue 20 (26th September 2022) - He, Shuijian; Wang, Xiang; Xiang, Guiming; Lac, Kevin; Wang, Changshui; Wang, Suning; Ding, Zhifeng
Abstract : Pure white electrochemiluminescence (ECL) was generated from a Pt(II) complex with coreactant persulfate (Pt1 /S2 O8 2‐ ) in dichloromethane (DCM) for the first time. It is plausible that the white light is a combination of dual emissions from the monomer excited state (blue) and excimer (red). The ECL was tunable from white to blue by simply changing the solvent from DCM to N, N‐dimethylformamide (DMF). The much brighter blue ECL in DMF is due to the regeneration loop for the monomer excited state through collisional interactions of Pt1 with the electrode at an elevated frequency. More information on this study can be found in the Research Article by Zhifeng Ding et al.